Timing of swarmer cell cycle morphogenesis and macromolecular synthesis by Hyphomicrobium neptunium in synchronous culture. - Wali, T M (1980)
The swarmer cycle of Hyphomicrobium neptunium consists of a temporal sequence of discrete developmental events. To time morphogenesis and to investigate modulations in macromolecular synthesis, we attempted methods for synchronous culture. During synchrony, swarmer maturation occurred over 32%, hyphal growth occurred over 36%, and bud maturation occurred over 32% of the time required to complete the swarmer cycle. Daughter cells were released after 265 min. Deoxyribonucleic acid replication was discontinuous, having a G1 period of approximately 180 min. In addition, ribonucleic acid and protein syntheses were depressed during the earlier phases of development.